Alteration of the platelet transcriptome in chronic kidney disease - Plé, Hélène; Maltais, Manon; Corduan, Aurélie; Rousseau, Guy; Madore, François; Provost, Patrick (Thrombosis and Haemostasis, 2012)
Bleeding and thrombotic disorders are major complications affecting patients with chronic kidney disease (CKD). Exposure of circulating platelets to uraemic toxins and contact with artificial surfaces during dialysis induce platelet abnormalities and alter the platelet proteome. We hypothesised that these changes may be subsequent to changes in the composition and/or regulation of the platelet transcriptome. In this study, we investigated the circulating platelets of 10 CKD patients (i.e. five chronic haemodialysis patients and five stage 4 CKD uraemic patients) and five age- and sex-matched healthy subjects. We observed an alteration of the platelet messenger RNA (mRNA) and microRNA transcriptome in CKD patients. Impaired in uraemic platelets, the levels of some mRNAs and of most microRNAs appeared to be corrected by dialysis, which is consistent with a beneficial effect of dialysis and a mRNA regulatory role of platelet microRNAs. Reduced in platelets of uraemic patients, phosphatidylcholine transfer protein (PCTP) and WD repeat-containing protein 1 (WDR1) were found to be regulated by microRNAs, the latter of which involving hsa-miR-19b, a microRNA increased in platelets of uraemic patients and involved in platelet reactivity. These results suggest that an alteration of microRNA-based mRNA regulatory mechanisms may underlie the platelet response to uremia and entail the development of platelet-related complications in CKD.
Keywords: Chronic kidney disease; platelets; gene expression; mRNA; microRNA